Prefrontal Ischemia in the Rat Leads to Secondary Damage and Inflammation in Remote Gray and White Matter Regions - Weishaupt, Nina; Zhang, Angela; Deziel, Robert A.; Tasker, R. Andrew; Whitehead, Shawn N. (Frontiers in Neuroscience, 2016)
Secondary damage processes, such as inflammation and oxidative stress, can exacerbate an ischemic lesion and spread to adjacent brain regions. Yet, few studies investigate how regions remote from the infarct could also suffer from degeneration and inflammation in the aftermath of a stroke. To find out to what extent far-remote brain regions are affected after stroke, we used a bilateral endothelin-1-induced prefrontal infarct rat model. Brain regions posterior to the prefrontal cortical infarct were analyzed for ongoing neurodegeneration using FluoroJadeB and for neuroinflammation using Iba1 and OX-6 immunohistochemistry 28 days post-stroke. The FJB-positive dorsomedial nucleus of the thalamus and retrosplenial area of the cortex displayed substantial neuroinflammation. Significant neuronal loss was only observed within the cortex. Myelin content within the FJB-positive internal capsule was negatively correlated with the size of the infarct, which, combined with microglial recruitment and activation, indicates remote white matter degeneration. These findings demonstrate that even regions far remote from an infarct are affected predictably based on anatomical connectivity, and that white matter inflammation is an integral part of remote pathology. The delayed nature of this pathology makes it a valid target for preventative treatment, potentially with an extended time window of opportunity for therapeutic intervention using anti-inflammatory agents.